ANALISIS BUSINESS LEVEL STRATEGY DAN DIVERSIFICATION PERUSAHAAN SAMSUNG - Adi Wilyanto; Angelina Julia Renaldi; Eni Valentina; Richmond Richmond; Rieza Melinda; Adi Neka Fatyandri (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2023)
The writing of the article "Analysis of Samsung Company's Business Level andDiversification Strategy" aims to analyze the Business Level and diversificationstrategy carried out by Samsung since its inception until now. The research methodused in analyzing this article is a qualitative method, where the data collection stageis through direct observation at Samsung outlets and online in the form of socialmedia, internet sites and so on. After obtaining the necessary information and data,the author describes descriptively the results of the analysis. The final result of theanalysis is that Samsung's business strategy has helped the company create a goodposition in the technology industry and the company is able to offer high-qualityproducts at competitive prices. The diversification carried out by the Samsungcompany involves expanding product and service offerings into new markets andindustries. In conclusion Samsung company carried out a clear and efficientbusiness level strategy. All the ideas and decisions made by the management teamare always planned for longer good and bad outcomes.Keywords: Descriptive, Diversification, Samsung, Qualitative Method.